2019
DOI: 10.1037/xhp0000693
|View full text |Cite
|
Sign up to set email alerts
|

Talker-specific pronunciation or speech error? Discounting (or not) atypical pronunciations during speech perception.

Abstract: Perceptual recalibration allows listeners to adapt to talker-specific pronunciations, such as atypical realizations of specific sounds. Such recalibration can facilitate robust speech recognition. However, indiscriminate recalibration following any atypically pronounced words also risks interpreting pronunciations as characteristic of a talker that are in reality because of incidental, short-lived factors (such as a speech error). We investigate whether the mechanisms underlying perceptual recalibration involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 80 publications
(191 reference statements)
3
17
0
Order By: Relevance
“…Moreover, when the mask was over the mouth throughout the duration of exposure for both clear and ambiguous tokens (Experiment 4), listeners demonstrated adaptation in line with biasing condition, suggesting that seeing the mask over the mouth throughout exposure did not alter categorization decisions. Our results converge with existing research demonstrating that listeners either ignored the external factor or that not all external factors are weighted equally in speech adaptation (e.g., Liu & Jaeger, 2019;Kraljic & Samuel, 2011;Drouin et al, 2018). However, our results diverge from previous research demonstrating that external cues can causally alter how listeners accommodate the input (e.g., Kraljic et al, 2008;McAuliffe & Babel, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Moreover, when the mask was over the mouth throughout the duration of exposure for both clear and ambiguous tokens (Experiment 4), listeners demonstrated adaptation in line with biasing condition, suggesting that seeing the mask over the mouth throughout exposure did not alter categorization decisions. Our results converge with existing research demonstrating that listeners either ignored the external factor or that not all external factors are weighted equally in speech adaptation (e.g., Liu & Jaeger, 2019;Kraljic & Samuel, 2011;Drouin et al, 2018). However, our results diverge from previous research demonstrating that external cues can causally alter how listeners accommodate the input (e.g., Kraljic et al, 2008;McAuliffe & Babel, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…However, not all instruction-based manipulations appear to influence phonetic recalibration in the same way. For example, in a series of experiments, Liu and Jaeger (2019) provided alternate causes for atypical speech productions: ambiguous speech in tongue twister contexts, ambiguous speech for a talker with a fast-speaking rate, and ambiguous speech for a talker who listeners were told was intoxicated. Participants demonstrated phonetic recalibration in each experiment and the magnitude of adaptation did not attenuate despite listeners having a clear factor (either implicit or explicit) for the ambiguity.…”
Section: Constraints On Phonetic Recalibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…One difference from BB08 is that our replications were conducted over the web. This decision was motivated by practical, rather than theoretical, considerations, in order to facilitate the recruitment of a large number of participants (see also Liu & Jaeger, 2018; 2019). However, web-based recruitment entails (a) a more heterogeneous participants group, (b) less control over the way participants approach the task, and (c) more variability in auditory equipment across participants.…”
Section: Discussionmentioning
confidence: 99%
“…Copious studies on pronunciation in relation to intelligibility and foreign accent have been sought, and the utmost of them focus on the pronunciation purely (Rahimi & Ruzrokh, 2016;Suntornsawet, 2019) and also on the perception of accented speech (Behrman et al, 2020;Sereno et al, 2016). Furthermore, several pieces of research about perception on pronunciation errors have been found related to accented speech on the level of segmental (Gao & Weinberger, 2018;Lindemann, 2017;Liu & Jaeger, 2019). Segmental errors of both consonants and vowels are the primary origin of the listeners' trouble to measure the speech's intelligibility (Levis, 2018).…”
Section: Introductionmentioning
confidence: 99%